1993
DOI: 10.1148/radiology.186.3.8430186
|View full text |Cite
|
Sign up to set email alerts
|

Phase III multicenter clinical investigation to determine the safety and efficacy of gadoteridol in children suspected of having neurologic disease.

Abstract: A phase III open-label clinical trial was conducted at 11 institutions to determine the safety and efficacy of gadoteridol in children suspected of having neurologic disease. One hundred three children were included in the safety analysis; 92 were evaluated for efficacy (76 intracranial and 16 spinal examinations). Three adverse events were reported in two children. All adverse events were considered minor and resolved spontaneously without treatment or sequelae. In a comparison of enhanced T1-weighted magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…No significant adverse clinical events or clinically important trends in vital signs have been reported in association with the use of Gd chelates in this patient group [33]. In addition, the use of gadopentetate dimeglumine is approved in Europe at doses up to 0.2 mmol/kg for CNS studies and body MRI in infants (day 1 of life).…”
Section: Tolerance and Adverse Eventsmentioning
confidence: 87%
“…No significant adverse clinical events or clinically important trends in vital signs have been reported in association with the use of Gd chelates in this patient group [33]. In addition, the use of gadopentetate dimeglumine is approved in Europe at doses up to 0.2 mmol/kg for CNS studies and body MRI in infants (day 1 of life).…”
Section: Tolerance and Adverse Eventsmentioning
confidence: 87%
“…In conclusion, while many studies have confirmed the "added value" of contrast-enhanced images for pediatric MRI (97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108), the question is whether or not routine contrast administration in children is warranted. Given that there appears to be an identical safety profile in the pediatric and adult populations, it seems reasonable to administer Gd-based agents to children in the same basic situations considered for adults, particularly in the evaluation of neoplastic or inflammatory disease.…”
Section: Pediatricsmentioning
confidence: 99%
“…The administration of exogenous MR contrast agents has been shown to improve contrast enhancement and the ability to distinguish pathologic tissue from normal tissue [1]. In addition to adult applications, MR contrast agents have also demonstrated clinical diagnostic utility in pediatric patients [2][3][4].…”
Section: Introductionmentioning
confidence: 99%